The effect of mixed fertilizers on the vegetative growth and reproductive characteristics of tomatoes (L. esculentum Mill) (International Journal of Biology and Chemistry, 2022)
The purpose of this study was to investigate how combination fertilizers based on seaweed liquid extract (SLF) and nitrogen fertilizer (PU) affected tomato vegetative development and reproductive characteristics (L. esculentum Mill). The mixed fertilizers had varying amounts of SLF and a constant amount of PU [(5% SLF + PU50), (10% SLF + PU50, 30% SLF + PU50), and (50% SLF + PU50)]. The greenhouse was used to study tomato growth and yield response to mixed fertilizer. The Randomized Complete Block Design (RCBD) was used for the experiment, with five replicates for each treatment. The data were analysed using variance analysis (ANOVA) and compared to a control that did not use fertilizer. The results revealed that the mixed fertilizers resulted in substantial increases in all the evaluated attributes. However, mixed fertilizer (10% SLF + PU50) produced the highest vegetation, flower, and fruit characteristics compared to the control plants and other treatments. These results clearly show that 10% SLF + PU50 is favourable for tomatoes.